2008
DOI: 10.1080/07373930802306953
|View full text |Cite
|
Sign up to set email alerts
|

CFD Evaluation of Droplet Drying Models in a Spray Dryer Fitted with a Rotary Atomizer

Abstract: Computational fluid dynamics (CFD) modeling of spray dryers requires a simple but sufficiently realistic drying model. This work evaluates two such models that are currently in discussion; reaction engineering approach (REA) and characteristic drying curve (CDC). Two versions of the CDC, linear and convex, drop in drying rate were included. Simulation results were compared to the overall outlet conditions obtained from our pilot-scale experiments. The REA and CDC with a linear drop in drying rate predicted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…4 (a) and (b) for four particle diameters of 17, 50, 75 and 100 μm which were selected to represent the behaviour of different particle size classes. The particle axial velocities are different from the gas velocities with the gas showing upward velocities outside of the central core region (also seen in simulations by Woo et al [13] ) in contrast to the particles which are predicted to travel downwards. In the core region of the chamber fewer data are shown for particle velocities because only a small number of particles entered this region due to the use of a hollow cone spray with a 76° spray angle.…”
Section: Radial Profiles Of Particle Axial Velocitymentioning
confidence: 80%
See 1 more Smart Citation
“…4 (a) and (b) for four particle diameters of 17, 50, 75 and 100 μm which were selected to represent the behaviour of different particle size classes. The particle axial velocities are different from the gas velocities with the gas showing upward velocities outside of the central core region (also seen in simulations by Woo et al [13] ) in contrast to the particles which are predicted to travel downwards. In the core region of the chamber fewer data are shown for particle velocities because only a small number of particles entered this region due to the use of a hollow cone spray with a 76° spray angle.…”
Section: Radial Profiles Of Particle Axial Velocitymentioning
confidence: 80%
“…Woo et al [13] simulated particle surface moisture contents using Reaction Engineering Approach (REA) and characteristic drying curve (CDC) methods and they found that both the models predicts almost similar particle moisture and trajectories. Recently, Jin and Chen [14] studied the effects of particle size on particle residence time using REA.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the flowfield in spray dryers by CFD methods has drawn a lot of attention in recent years [10e21]. These studies cover flow patterns in the dryer [10,13e16,20], wall deposition [11,12,18,21], agglomeration [17] and particle behaviors [19]. The present study uses the same solver as the one in our previous work in Refs.…”
Section: Introductionmentioning
confidence: 94%
“…In CDC it is assumed that, for each average moisture content, exists a corresponding specific relative drying rate. Woo et al (2008) compared with experiments droplet drying of sugar solutions using CDC and REA techniques and showed good accuracy of both methods.…”
Section: Drying Kineticsmentioning
confidence: 99%